Mobility and stasis: Ageing abroad in Abla Farhoud's Le Bonheur a la queue glissante. Issue 1 (July 2017) - Averis, Kate
Abstract : Transnational mobility constitutes a frequent feature of much contemporary francophone women's writing whose origins lie in territories with historical links to French colonial power. Yet whether configured as exile, migration, travel, or other, the experiences of transnational mobility described in postcolonial francophone women's writing frequently focus on protagonists in childhood and early adulthood: the experiences and challenges of the exile, migrant, or traveller are seldom imagined in these texts as those of an individual in late adulthood or old age. This article analyses the intersection of ageing, mobility, and femininity in Abla Farhoud's Le Bonheur a la queue glissante (1998), one of few narratives in French to broach the question of female ageing in migration. Reading the text in light of Sara Ahmed's insights into the relationship between strangers, embodiment, and community (2000), the analysis reveals Farhoud's challenge to any easy correlation between mobility and youth, and stasis and old age, and presents the potential of narratives of female ageing in migration as an underexplored space of dynamic space of growth and change that does not overlook the real bodily and subjective challenges of women's ageing.